2019
DOI: 10.1038/s41598-019-49419-z
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF and GM-CSF Modify Neutrophil Functions at Concentrations found in Cystic Fibrosis

Abstract: The role of colony stimulating factors (CSFs) in cystic fibrosis (CF) circulating neutrophils has not been thoroughly evaluated, considering that the neutrophil burden of lung inflammation in these subjects is very high. The aim of this study was to assess granulocyte-CSF (G-CSF) and granulocyte-macrophage-CSF (GM-CSF) levels in CF patients in various clinical conditions and how these cytokines impact on activation and priming of neutrophils. G-CSF and GM-CSF levels were measured in sputum and serum samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…We therefore also evaluated the lung concentrations of pro-inflammatory cytokines (IL-1 cytokine family, IL2, TNFa, IFNg, GM-CSF, G-CSF, etc.) and CC-chemokines involved in the recruitment of mononuclear cells (MCP-1, MIP-1a and MIP-1b) that play a role in pathogenesis and inflammatory pathology in the lung (29)(30)(31). We observed no statistically significant differences in pro-inflammatory cytokine or CC-chemokine concentrations among SARS-CoV-2 infected macaques either untreated or treated with HCQ (Figs.…”
Section: Resultsmentioning
confidence: 69%
“…We therefore also evaluated the lung concentrations of pro-inflammatory cytokines (IL-1 cytokine family, IL2, TNFa, IFNg, GM-CSF, G-CSF, etc.) and CC-chemokines involved in the recruitment of mononuclear cells (MCP-1, MIP-1a and MIP-1b) that play a role in pathogenesis and inflammatory pathology in the lung (29)(30)(31). We observed no statistically significant differences in pro-inflammatory cytokine or CC-chemokine concentrations among SARS-CoV-2 infected macaques either untreated or treated with HCQ (Figs.…”
Section: Resultsmentioning
confidence: 69%
“…The cleavage of another chemokine receptor, CXCR1, has also been linked to impaired bacterial clearance in CF [164]. Other pro-inflammatory signals, such as ROS [165] and colony-stimulating factors [166], are significantly raised in CF; likewise, levels of the bioactive fragment of collagen called proline-glycine-proline (PGP) which is generated by the activity of both prolylendopeptidase and matrix metalloproteinase-9 (MMP9), are also raised [167]. As PGP acts as a stimulant of neutrophil migration into tissues, as well as inducing epithelial remodelling, it has been suggested that the raised levels of PGP found in the lungs of children with CF may exacerbate the inflammatory phenotype found in these patients [167].…”
Section: Neutrophilsmentioning
confidence: 99%
“…In some respects, this can also be said of increased neutrophil apoptosis as a result of decreased levels of IL-6 and IL-8, which would otherwise increase neutrophil survival. However, decreased neutrophil survival following AZM administration also appears to be mediated by the inhibition of GM-CSF [ 155 , 156 ]. This cytokine regulates many aspects of neutrophil function and decreased levels inhibit neutrophil priming, which is important in the development of ARDS [ 155 ].…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%